PERAN BADAN LAYANAN UMUM UNIT PELAKSANA TEKNIS DINAS (BLU UPTD) TERMINAL MANGKANG DALAM PENYELENGGARAAN TRANSPORTASI PUBLIK KHUSUSNYA BUS RAPID TRANSIT (BRT) TRANS SEMARANG DI KOTA SEMARANG - Ardhianto Fajar Rizky; Ari Subowo (Journal of Public Policy and Management Review, 2016)
In accordance with Law No. 22 Year 2009 regarding Traffic and Road Transportation Article 158 Paragraph (1) "The government guarantees the availability of Transport Bulk-based way to meet the needs of the transport of public transport in urban areas." So rather than the intent and purpose of the Act, the Government Semarang City develop BRT (Bus Rapid Transit) Trans Semarang as a mass-based public transport modes. BLU UPTD Terminal Mangkang a manager of BRT Trans Semarang, based on the Decree of the Mayor of Semarang Number: 551.2 / 147 Year 2010 regarding Stipulation UPTD Terminal Mangkang Semarang as business BRT Trans Semarang and the Decree of the Mayor of Semarang Number: 551.2 / 238 of 2010 on the establishment of UPTD Terminal Mangkang Semarang as the Public Service Board. The purpose of this study is to describe and analyze the role of and to describe the barriers related to the role that occur in the administration of the Public Transport especially BRT Trans Semarang in Semarang conducted by BLU UPTD Mangkang Terminal. This study uses a descriptive qualitative research design with an informant of the Head of BLU UPTD Terminal Mangkang, Head of subsection Planning and Evaluation Dishubkominfo Semarang, Divison Head of Infrastructure Planning Bappeda Semarang, PT. Trans Semarang and informant BRT Trans Semarang service users. The analysis process is done by identifying the related role of constraints and discussed through theoretical study and the sources of the data found. Based on the research results obtained BLU UPTD Terminal Mangkang has been cartying out a role in accordance with the duties and functions as the manager of BRT Trans Semarang, and can be explored on barriers roles occurs. Advice given over to repair shortcomings related to the role and improving the quality and quantity of services BRT Trans Semarang.